A Comparative Study of Serum Magnesium, Copper and Serum Total Cholesterol in Type 2 Diabetes Mellitus with and Without Retinopathy and Healthy Controls - Mannava Prasanthi Srikanth (Asian Journal of Medical Research, 2019)
Background: Type II Diabetes Mellitus (DM) is a metabolic disorder primarily characterized by hyperglycemia caused by insulin resistance and/or relative insulin deficiency. Complications of the diabetes are the major cause of morbidity and mortality in persons with type II DM. Magnesium and copper are divalent cations. Magnesium is the fourth most abundant cation in the human body and the second most abundant intracellular cation. It serves as a cofactor for all enzymatic reactions that require ATP and is a key component in various reactions that require kinases (300 enzymes). In the current study we plan to bring the relationship between Copper, Magnesium and Total Cholesterol and their role in the development of diabetic retinopathy. Subjects and Methods: The study was carried out on a total of 90 subjects included over a period of one year. 30 were confirmed cases of Type II DM with retinopathy patients and 30 were age matched Controlled Diabetes without retinopathy, and 30 were normal healthy controls. Informed consent was obtained from each subject. The subject’s medical history was recorded according to the questionnaire (proforma-see annexure) all the subjects before any investigations were carried out on them. Based on the analysis of medical history, clinical examination and investigation results the patients were grouped. Results: On comparison with healthy controls and Diabetes mellitus without retinopathy we found there is significant(p<0.05) increase in fasting blood glucose, serum copper, triglycerides and total cholesterol. No significant change is found in serum magnesium. On comparison with healthy controls in Diabetes mellitus with retinopathy we found there is significant (p<0.05) increase in fasting blood glucose, serum copper, triglycerides, total cholesterol and LDL cholesterol. Significant (p<0.05) decrease in serum magnesium and HDL cholesterol is found in serum magnesium. Conclusion: The serum magnesium levels were decreased (hypomagnesaemia) in diabetic retinopathy and were significantly correlated (p=0.022) as compared to controls. The copper levels were higher in diabetic retinopathy and correlated highly significant as compared to control (p<0.001). The serum concentration of TC and LDL showed increase in diabetic retinopathy and highly significantly correlated (p<0.001) as compared to controls where as there was mild increase in serum TG but found to be highly significantly correlated (<0.001).